Copper-Promoted Dimerization of Benzyl Thiocyanates to Access Functionalized Bibenzyls - Singh, Sandeep; Ranjan De, Saroj (Synlett, 2024)
The synthesis of bibenzyl derivatives holds significance in organic chemistry due to their diverse pharmacological and synthetic applications. Herein, we report a novel copper-promoted dimerization reaction for the efficient synthesis of functionalized bibenzyls from benzyl thiocyanates. The coupling reaction proceeds under aerobic and mild conditions through a cascade C–S bond cleavage in one pot. Diverse substituents, including electron-withdrawing groups on the aryl ring, are well tolerated to afford the desired products in moderate to good yields. The developed protocol could be utilized to obtain the cross-coupling product from two different electron-deficient benzyl thiocyanates.
Keywords: bibenzyls; benzyl thiocyanates; homocoupling; cross-coupling; C–S bond cleavage